(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Blunt abdomen trauma is common in surgical emergencies. Faster detection of intra-abdominal damage in BAT patients using a FAST scan and CT scan can lead to early treatment, reducing complications associated with late detection. This study aims to evaluate the diagnostic accuracy of FAST scans compared to CT scans in detecting intra-abdominal injuries. Methodology: The study, conducted at Lahore General Hospital’s Emergency Department from July 3, 2024, to January 2, 2025, enrolled 366 subjects meeting inclusion criteria. Patients had initial FAST exams and subsequent CT scans. FAST scans, performed by supervised residents using SAOTE MYLAB SEVEN, focused on detecting free intra-abdominal fluid in three pouches. Positive FAST results indicated fluid presence, leading to CT confirmation. Regardless of USG readings, all patients underwent FAST to compare outcomes and assess injuries for recording alongside patient details in a study proforma. Data was analyzed using SPSS V-20 for diagnostic measures. Results: In this study, 336 patients were enrolled meeting the criteria. 66.7% were males and 33.3% were females. Ages ranged from 14 to 50 years, with a mean of 32.3±12.6 years. The study found FAST scan sensitivity at 94.5%, specificity at 80.6%, PPV at 95.5%, NPV at 86.9%, and accuracy at 91.9% for identifying intra-abdominal injury positively. Conclusion: The FAST scan shows diagnostic accuracy similar to CT scans, based on local and international data, making it useful for triaging blunt abdominal trauma patients.